2019
DOI: 10.1159/000496694
|View full text |Cite
|
Sign up to set email alerts
|

Transplant of Adult Bone for Reconstruction of a Large Post-Traumatic Cranial Defect in a Very Young Baby

Abstract: Large cranial defects in very young patients are challenging. The ideal material for cranioplasty in this age group has not yet been identified. Cryopreserved autologous bone presents very high rates of failures, acrylic resins pose a number of compatibility problems, bioceramics may be contraindicated, and autografts may be not adequate for repair of large defects. We present an 18-month-old baby with a large post-traumatic cranial defect which was repaired by assembling a new bone flap on a sterile stereolit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…In addition, from the animal experiments on quinolone antibiotics, it was found that young animals taking quinolone antibiotics would produce cartilage damage to joint tissue, so children, pregnant and lactating women should be forbidden levofloxacin [ 32 35 ]. At the same time, because levofloxacin belongs to quinolones antibiotic effect, from this group of cases cure effect and ADRs of reaction after taking levofloxacin, static drop 1- or 2-times daily fee sand star of left oxygen drugs for prevention of postoperative infection, there was no significant difference, and oxygen cost effect of medication to reduce the incidence of ADR is safer and more effective [ 36 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, from the animal experiments on quinolone antibiotics, it was found that young animals taking quinolone antibiotics would produce cartilage damage to joint tissue, so children, pregnant and lactating women should be forbidden levofloxacin [ 32 35 ]. At the same time, because levofloxacin belongs to quinolones antibiotic effect, from this group of cases cure effect and ADRs of reaction after taking levofloxacin, static drop 1- or 2-times daily fee sand star of left oxygen drugs for prevention of postoperative infection, there was no significant difference, and oxygen cost effect of medication to reduce the incidence of ADR is safer and more effective [ 36 39 ].…”
Section: Discussionmentioning
confidence: 99%